El incumplimiento de la reparación integral a la víctima y su incidencia en la ejecución de penas, cantón Guaranda, 2022. - Parra Santillán, Damián Alexander (2024)
The present curricular research project has as its object of study: to carry out a legal and field investigation on the non-compliance of the integral reparation to the victim and its incidence in the execution of sentences, in the Guaranda canton, Bolívar Province, in the year 2022. To achieve this objective, the deductive research method was used, which allows starting from the general constitutional considerations and the jurisprudence on human rights of persons deprived of liberty that admits a particular legal analysis on the applicable criteria for compliance of penalties under the open and semi-open regimes and guarantee comprehensive reparation to the victims. For the development of the research, it had a bibliographic approach in terms of the theoretical framework and a quantitative approach in field research, where we worked with a population of prison judges and people deprived of liberty, whose sample meets the inclusion criteria and beneficiaries direct and indirect. As results valid criteria were obtained that make viable the right of persons deprived of liberty to benefit from prison regimes under constitutional principles and rights to guarantee comprehensive reparation to victims of criminal offenses and, the social and economic reintegration of people in compliance of the condemnation constitutional rights that prevail before any legal regulation and decision of the state power. It was established as a conclusion, that the failure to provide comprehensive reparation to the victim affects the exercise of the right to benefit from the open or semiopen regime given the legal threat of initiating a new criminal proceeding for contempt of authority. Therefore, it is recommended an adaptation to the legal norm against the supremacy of the Constitution that guarantees the resocialization of the convicted person and decreases his recidivism. Keywords: Comprehensive reparation, penitentiary regime; execution of sentences.